KOMPETENSI PEDAGOGIK MAHASISWA DALAM MENGELOLA PEMBELAJARAN TEMATIK INTEGRATIF KURIKULUM 2013 PADA PENGAJARAN MICRO DI PGSD UAD YOGYAKARTA - Fitri Indriani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
This study aims to determine; (1) The pedagogical competence of students in managing integrated thematic learning curriculum in 2013 on micro teaching; (2) determine the barriers faced by students in managing integrated thematic learning curriculum in 2013 on micro teaching. This type of research is a field research using qualitative approach. The experiment was conducted in PGSD UAD Yogyakarta for six months. Technique of determining the source of the data by purposive sampling. The selected data source in this study are listed VI semester students active as a student and is implementing micro teaching. The data collection techniques is done by observation, interview and documentation. The validity of the data using triangulation, and data analysis was done descriptively kualitatif.Hasil research shows that; (1) The pedagogical competence of students in managing integrated thematic learning curriculum in 2013 on micro teaching is good. It is shown from the four aspects of pedagogical competence are the focus in the research, overall it can be displayed properly. Organized learning such as active, democratic and fun and in accordance with the planned RPP. RPPyang drafted in accordance with the standards process, which made already measurable indicators and have been using operational verbs (Marines). Step-by-step learning activities describe active learning, designing strategies and the use of media is quite varied, the draft assessment is appropriate and includes all indicators and describes otentik.Dalam implement thematic learning assessment is in conformity with the characteristics of the integrated thematic learning student-centered, there are interactive. The transfer of subjects one to the other subjects are not too visible. The scientific approach has been applied the observe, ask, reasoning, associate and communicate. Evaluations carried out during the learning process and at the end of the learning activities by developing authentic assessment and measures three aspects of the cognitive, affective and psychomotor; (2) the barriers faced by students in managing integrated thematic learning curriculum teaching in 2013 at the micro, among others; develop assessment instruments; linking indicators each subject according to the theme; removal of subjects one to the other subjects; make APE according to the theme; developing material.